Strategi Intervensi Operasional dan Digital untuk Peningkatan Keberlanjutan UMKM Kuliner di Lamongan : Penelitian - Miftahqul Mauliddia Rakhmawati; Nur Indah Charisma Zogi Martana; Habib Ramadhan; Rizky Wahyudha Rosiawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a vital foundation for the stability and acceleration of national economic growth, reflected in the growth figure of Indonesia’s Gross Domestic Product (GDP) at 5.12% in the Second Quarter of 2025. The ready-to-eat food sector, especially the seblak business, is a highly dynamic and prospective segment. This community service report presents the results of mentorship focused on Seblak Lahrisa Prasmanan MSME in Lamongan, with the main goal of providing solutions to four constraints that hinder business growth. These challenges include service flow inefficiency which creates a queue buildup (bottleneck) at the cashier area, the absence of financial statement documentation leading to profitability ambiguity, constraints in finding and recruiting adequate human resources, and the urgency to expand market reach through a digital platform (website). The implemented solution interventions include designing an operational flowchart to solve the queuing problem, creating a simple financial reporting template based on Microsoft Excel to achieve financial transparency, reformulating recruitment policies to be more open and competence-oriented, and developing a website as a digital ordering center. The achievement of this activity is the availability of visual and analytical instruments for the MSME to enhance operational performance, financial accountability, the effectiveness of the HR management system, while simultaneously creating a solid foundation for digital market expansion.